DIFFERENCES EFFECT OF PROGRESSIVE MUSCLE RELAXATION THERAPY AND SUPPORTIVE THERAPY ON PARENTS ANXIETY WITH CHILDREN HOSPITALIZATION AT RSUD.DR.R.SOEDJONO SELONG EAST LOMBOK - Farida Maemunah Martiningsih; Retty Ratnawati; Asti Melani Astari (Journal of Nursing Science Update (JNSU), 2018)
Hospitalization is an issue that is not expected by everyone, especially children, because they have to undergo some procedure of action and examination. This problem causes anxiety and stress for parents, one of which is marked by muscle tension. This problem can be overcome by nursing actions using Progressive Muscle Relaxation Therapy and Supportive Therapy. The study aims to distinguish the influence of Progressive Muscle Relaxation Therapy and Supportive Therapy in reducing the anxietyÂ parents with children undergoing hospitalization. The research applied quantitative approach with Quasi experimental pre post test, the number of respondents 25 pairs of parent each group, using purposive sampling technique. The research location at RSUD.Dr.R.Soedjono Selong, East Lombok regency on August to October 2017. Based on the result of the study showed decrease of anxiety score the Progressive Muscle Relaxation Therapy was lower than Supportive Therapy, which was 6.30 < 10.44, and t value was 0.000. The used of Progressive Muscle Relaxation Therapy was significant which p value was 0.000. The conclusion of the study results There was a difference in effect between Progressive Muscle Relaxation Therapy and Supportive Therapy in lowering parental anxiety levels, with the results of Progressive Muscle Relaxation Therapy is better to lower parental anxiety than Suportive Therapy. Further research needs to be developed modification of Progressive Muscle Relaxation Therapy versus Supportive Therapy in other groups.Â